Use substitution to solve the system.  x=3y+7 and 3x-4y=16


x=
y=

Answers

Answer 1
Answer: First we already know x, so we can put it into the other equation like so:

3(3y+7)-4y=16

Then we can solve it.

9y+21-4y=16

5y=-5

y=-1

Then we can find x.

x=3y+7

x=3(-1)+7

x=-3+7

x=4

Hope I helped!
Answer 2
Answer: x = 3y + 7
3x - 4y = 16

Substituting the value of x,

3(3y + 7) - 4y = 16

9y + 21 - 4y = 16

5y + 21 = 16

5y = -5

Thus, y = -1.

Substituting the value of y,

x = 3y + 7

x = -3 + 7

Thus, x = 4.

Thus, x = 4, and y = -1

Related Questions

If the zeroes of the polynomial x² + px + q are double in value to the zeroes of 2x² - 5x - 3, find the value of and .
Mara carried water bottles to the field to share with her team at halftime. The water bottles weighed a total of 60x2 + 48x + 24 ounces. Which factorization could represent the number of water bottles and weight of each water bottle? 6(10x2 + 8x + 2) 12(5x2 + 4x + 2) 6x(10x2 + 8x + 2) 12x(5x2 + 4x + 2)
If f(x) = 3x + 2 and g(x) = x2 + 1, which expression is equivalent to (fxg) (x)?
Divide 25kg in in a ratio of 2:3:5
2. If a circle has the diameter of 8, what is the circumference?

A juice stand uses 11 cups of strawberries to make 6 pitchers of juice. What is true about the number of cups of strawberries in each pitcher?

Answers

use ratio and proportion 11/6=x/1 cross multiply x= 15/6 which is approximately 2 cups
There is less than one cup of strawberries in one pitcher of juice.

What is the distance between points (3,8) and (-9,-8)5
10
15
20

what is the distance between points (2,6) and (5,2)
3
4
5

what is the distance between points (21,16) and (9,11)
13
12
22
24

Answers

It is better to graph these points, to easily understand that the distance of the two points form the hypotenuse of the right triangle.  We need to use the Pythagorean theorem to solve for the distance of the two points.

a² + b² = c² ; a = x value ; b = y value

1) (3,8) and (-9,-8)
a = 3 - (-9) = 3 + 9 = 12 ⇒ 12² = 144
b = 8 - (-8) = 8 + 8 = 16 ⇒ 16² = 256 ⇒⇒ 144 + 256 = 400 ; c = √400 = 20

2) (2,6) and (5,2)
a = 2 - 5 = 3 ⇒ 3² = 9
b = 6 - 2 = 4 ⇒ 4² = 16 ⇒⇒ 9 + 16 = 25 ; c = √25 = 5

3) (21,16) and (9,11)
a = 21 - 9 = 12 ⇒ 12² = 144
b = 16 - 11 = 5 ⇒   5² =    25 ⇒⇒ 144 + 25 = 169 ; c = √169 = 13

Write this equation: 8.75×10−4 in standard notation

Answers

To write in standard notation means writing the equation "normally", solving it and then writing the resulting number in its extensive form with all explicit digits. 10^-4 is 0,0001, so: 8,75x0,0001=0,000875

Given x varies inversely with y and xy = 2, what is the value of x when y = 1?a) -1

b) 1/2

c)1

d) 2

Answers

Answer is (d).

Let's take the constant as K.
x=K. (1/y)----(1)'
K= xy
so; according to the data given above K=2.

Let's substitute K=2 & y=1 to ----(1)'

x=2x (1/1)
x= 2×1
so x = 2... :)



Determine which relation is a function. A.{(–4, 3), (–2, 3), (–1, 2), (2, 5), (3, 2)}

B.{(–4, 1), (–2, 3), (–2, 1), (–1, 5), (3, 2)}

C.{(–4, 1), (–2, 3), (–1, 2), (3, 5), (3, 2)}

D.{(–4, 1), (–2, 3), (–1, 1), (–1, 5), (3, 2)}

Answers

The A is a function, because all the values of the independent variable (the first value of the ordered pairs) are related to only one value, i.e. have only one image.

In B - 2 has two different images: 3 and 1. That makes that this is not a function.

In C, 3 has two different images: 5 and 2. That makes that this is not a function.

In D, - 1 has two different images: 1 and 5. That makes that this is not a function.

Which shows one way to determine the factors of x3 – 9x2 + 5x – 45 by grouping?x2(x – 9) – 5(x – 9)
x2(x + 9) – 5(x + 9)
x(x2 + 5) – 9(x2 + 5)
x(x2 – 5) – 9(x2 – 5)

Answers

x³ - 9x² + 5x - 45

x²(x - 9) - 5(x - 9) ⇒ x³ - 9x² - 5x + 45 INCORRECT
x²(x + 9) - 5(x + 9) ⇒ x³ + 9x² - 5x - 45 INCORRECT

x(x² + 5) - 9(x² + 5) ⇒ x³ + 5x - 9x² - 45 CORRECT
It just needs to be rearranged.

x(x² - 5) - 9(x² - 5) ⇒ x³ - 5x - 9x² + 45 INCORRECT

The answer choice which shows a way to determine the factors by grouping is; x(x² + 5)9(x² + 5).

Which shows one way to determine the factors of x3 – 9x2 + 5x – 45 by grouping?

According to the task content, the factors of the expression are to be determined by grouping.

On this note, one way to group the factors would be;

x³ + 5x - 9x² -45

Upon factorisation;

x(x² + 5) – 9(x² + 5).

Read more on factorisation by grouping;

brainly.com/question/12675337

#SPJ5